EspañolCharacterization of canine neoplasms diagnosed by histopathology at the laboratory of Histology and Pathology Veterinary of the Universidad Peruana Cayetano Heredia: period 2003-2015 - Aco Alburqueque, Renato (2020)
The purpose of this study was to determine the frequency of canine neoplasia between 2003 and 2015 diagnosed by histopathology at the Laboratory of Veterinary Histology and Pathology from the Cayetano Heredia Peruvian University. A total of 2620 cases were analyzed which only the 46.3% of them were included in this study. The morphologic diagnosis of neoplasia was reclassified according to "International Histological Classification of Tumors of Domestic Animals" (WHO-AFIP), excluding mammary tumors which were classified according to Goldschmidt et al. (2011). Sex, age, breed, anatomical location of sample, morphological or clinical features and grade of malignancy were recorded and analyze by statistical analysis. Squamous cell carcinoma was the most frequent neoplasia observed in dogs, being female and geriatric patients the most affected (60.7 and 54.4% respectively). Mixed breed showed a higher prevalence of neoplasia (35.7%); furthermore, the presence of a tumor was the most common clinical presentation (93.7%), mainly located in the integumentary system (51.2%) and mammary gland (23.6%). The 72.1% of neoplasms exhibited malignancy features. An association was found with the presence of an inflammatory process with the malignancy of the neoplasia. A further evaluation by immunochemistry is required in order to obtain an accurate diagnosis.